2005
DOI: 10.1086/427290
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Staphylococcus aureus Strains Carrying Panton-Valentine Leukocidin Genes and the Development of Deep-Seated Follicular Infection

Abstract: PVL gene-positive S. aureus strains are involved in the development of multiple furuncles with more-intense erythema, particularly in healthy young adults. An understanding of the characteristics of furuncles due to PVL gene-positive strains might be useful for preventing the development of the severe systemic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 14 publications
8
70
2
2
Order By: Relevance
“…One of the toxins, Panton-Valentine leukocidin (PVL) is associated with human pyogenic necrotizing skin infections such as furuncles, cellulitis, and abscesses, and more severe septic infections such as osteomyelitis, bacteremia, purpura fulminans, and necrotizing pneumonia (1)(2)(3)(4)(5)(6)(7)(8). PVL with γ-hemolysins (HlgA/HlgB and HlgC/ HlgB) and LukE/LukD belongs to the bicomponent pore-forming leukotoxin family (9)(10)(11)(12)(13)(14), which are thought to contribute to virulence in various infection models (15)(16)(17)(18), although some groups disagree (19,20).…”
mentioning
confidence: 99%
“…One of the toxins, Panton-Valentine leukocidin (PVL) is associated with human pyogenic necrotizing skin infections such as furuncles, cellulitis, and abscesses, and more severe septic infections such as osteomyelitis, bacteremia, purpura fulminans, and necrotizing pneumonia (1)(2)(3)(4)(5)(6)(7)(8). PVL with γ-hemolysins (HlgA/HlgB and HlgC/ HlgB) and LukE/LukD belongs to the bicomponent pore-forming leukotoxin family (9)(10)(11)(12)(13)(14), which are thought to contribute to virulence in various infection models (15)(16)(17)(18), although some groups disagree (19,20).…”
mentioning
confidence: 99%
“…Not only does antibiotic therapy predispose patients to colonization with MRSA, but it also increases the risk of invasive disease and infection. Other host factors associated with progression from colonization to infection include recent hospitalization, preceding surgical or wound debridement, and the number of invasive procedure 4 . In the present study, the antibiotic sensitivity results showed that all MRSA isolates were significantly more resistant to various antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Also it can cause a variety of infections ranging from relatively minor skin infections, to life-threatening systemic illnesses such as meningitis, endocarditis, septic arthritis, osteomyelitis, subcutaneous or visceral abscesses, toxic shock syndrome (TSS), Staphylococcal scalded skin syndrome (SSSS) and septicemia. Staphylococcus aureus infections are associated with morbidity in hospitals and community 4 . Serious endemic and epidemic Methicillin Resistant Staphylococcus Aureus (MRSA) infections occur globally.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging view that the biological role of PVL may be to allow direct invasion of human skin so that CA-MRSA may disseminate via clinically active skin infection rather than relying solely on asymptomatic colonization of mucus membranes [33][34][35][36][37]. In support of this view are reports that PVL is less likely to be present in blood culture isolates than isolates obtained from aggressive skin infections or necrotizing pneumonia [26,29].…”
Section: Discussionmentioning
confidence: 99%